Narrativas Sobre Las Dinámicas Familiares Frente a un Posible Diagnóstico De Pre-Diabetes y Sobrepeso En Hijos de un Grupo de Madres Cuidadoras (2019)
This investigation Antonio Nariño derived from the project has been realized for the Faculty of Psychology of the University macro close to the Faculty of Medicine, Sciences and Psychology The field of investigation calls: Narratives on a possible diagnosis of pre - diabetes and overweight in children of a group of mothers carers of the city of Bogota. This investigation tries to analyze the stories of the group in mention. For the previous thing, there was designed a qualitative methodology in which there were born in mind references of the systemic thought, from the perspective in situations that turn into experience, when the human being believes narratives to speak it brings over of them.